Investigating the effect of corporate governance on audit quality and its impact on investment efficiency - Walid Shehata Mohamed Kasim Soliman (Investment Management & Financial Innovations, 2020)
There is an academic discussion about investment efficiency, regarding its determinants and effects. Corporate Governance (CG) and Audit Quality (AQ) are determinants of investment efficiency The main objective of the article is to investigate the effect of CG and AQ on investment efficiency, this objective is divided into sub-objectives: to investigate the direct effect of CG on AQ, AQ on investment efficiency, and CG on investment efficiency. Moreover, the indirect effect of CG on investment efficiency through AQ as a mediator variable. This paper focuses on non-financial listed firms in the Egyptian Stock Exchange (EGX), especially firms recorded in EGX 100 for four years’ period (2013–2018), for 103 firms and 412 completed observations. The researcher uses Structural Equation Modeling (SEM) through SmartPLS software. The paper shows evidence that management that has good CG mechanisms obtains a suitable atmosphere to prepare transparent financial statements, which helps enhance the auditor’s role and improve AQ. Improving AQ lowering IA, which increases the trust of investors in management decisions, this leads to reduce pressure on management and improve efficiency of investment decisions. Having good CG mechanisms provides management with a good atmosphere to make right investment decisions, and having good CG mechanisms increases AQ, which helps management to have a good environment to make investment decisions with higher efficiency, or in other words, there is a significant and positive effect of integration between CG and AQ on investment efficiency.